Evaluation of Correlation between Serum Free Light-Chain Assay and Bone Marrow Study in Multiple Myeloma Patients - Fatemeh Zamani; Mansoureh Shokripour; Maral Mokhtari (International Journal of Hematology-Oncology and Stem Cell Research, 2021)
Background: Multiple myeloma is a hematologic malignancy manifested by the secretion of abnormal immunoglobulin. Different methods have been described for diagnosis and patient response to management. Serum free light-chain assay is recently approved in the diagnosis of multiple myeloma patients.